2016
DOI: 10.3892/or.2016.5218
|View full text |Cite
|
Sign up to set email alerts
|

Propofol inhibits the growth and survival of gastric cancer cells in vitro through the upregulation of ING3

Abstract: Propofol is one of the most extensively used intravenous anesthetic agents and it can influence the biological behavior of gastric cancer. However, the underlying mechanism is poorly understood. In the present study, we found that propofol significantly inhibited cell proliferation, invasion and migration, and also promoted apoptosis in gastric carcinoma cell lines SGC-7901 and MGC-803, as detected using MTT, colony formation and flow cytometry assays, respectively. Moreover, propofol (10 and 20 µM) markedly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 28 publications
3
55
0
Order By: Relevance
“…Yang et al. provided evidence that propofol inhibited the growth and survival of gastric cancer cells in vitro through the up‐regulation of ING3. Tan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al. provided evidence that propofol inhibited the growth and survival of gastric cancer cells in vitro through the up‐regulation of ING3. Tan et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its anesthetic advantages, accumulating clinical evidence demonstrates that cancer patients receiving propofol-paravertebral anesthesia during cancer surgery have reduced risk of recurrence and metastasis (19). In addition, studies have shown that propofol exhibits potent antitumor activity in a variety of human cancer cell lines, including lung cancer cells (20), colon carcinoma cells (21), cervical cancer cells (22), pancreatic cancer cells (23) and gastric cancer cells (24), through different molecular mechanisms. However, the effect of propofol on Wnt signaling and glioma cell growth remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It can extract on lymphocytes apoptosis inducton, natural killer (NK) cytotoxicity inhibition and cytokines release alteration by NK cells in response to malignant cells, ultimately contributing to the development of migration and recurrence postoperatively [35]. However, as the most popular and common choice in TIVA, propofol has been considered to have predominately anticancer effects [10][11][12][13]. It can boost immune functions of the body and thus inhibit the cancer spread and metastasis [10][11][12][13].…”
Section: Publication Biasmentioning
confidence: 99%
“…However, as the most popular and common choice in TIVA, propofol has been considered to have predominately anticancer effects [10][11][12][13]. It can boost immune functions of the body and thus inhibit the cancer spread and metastasis [10][11][12][13]. Especially, propofol infusion anaesthesia has been found to modulate the Th1/ 2 balance by increasing the IFN-γ/IL-4 ratio in vitro [34].…”
Section: Publication Biasmentioning
confidence: 99%
See 1 more Smart Citation